Development and Validation of Kid Tsu Chu Futbol Games for Character Development - Sulistiyono, Sulistiyono (Universitas Negeri Semarang, 2017)
This research aims to develop and validation games to develop character in the students Football School under 12 years age group. This study was conducted using R and D. This study produced a product in the form of games related to the process of training, but can be used to develop the student’s character. Games that resulted from this research given the name “Tsu Chu Kid Futbol Games For Character Development”. Games have the flexible nature can be placed at the warm-up, core, and cooling at a football training process. The game must have at least two training purposes with the provisions of the first objective should be able to develop the character, and the second objective can develop one component among the components of the physical, technical, or tactics.